Untangling the Red Thread: How Linguistics Influences Culture and Identity - Fitriya (Contemporary Journal of Applied Sciences, 2025)
This study aims to examine how linguistics influences culture and identity in modern society. Through a qualitative approach, data were collected using text analysis methods, semi-structured interviews, and focus group discussions involving individuals from various backgrounds. The results of the analysis show that language does not only function as a means of communication, but also as a mirror that reflects the cultural values and social identities of individuals. It was found that language can strengthen collective and individual identities, and plays an important role in the process of cultural exchange. However, the use of language can also create challenges related to stereotypes and social hierarchies. These findings emphasize the importance of understanding the relationship between language, culture, and identity in a changing global context.